Pengaruh Metode Mudarosah terhadap Peningkatan Keterampilan Membaca Al-Qur’an Peserta Didik - Nur Zaini; Sri Utami (Fakultas Agama Islam Universitas Billfath, 2022)
This study aims to first describe the application of the mudarosah method, to identify the level of Qur'an reading skills of class VIII students, and to measure the effectiveness of the mudarosah method in improving students' reading skills of the Koran VIII. This type of research uses correlative quantitative research. The data collection methods used are questionnaires and documentation. The object of this research is students with a population of 57 and a sample of 48 respondents. The data analysis technique used in the first and second problem formulations is using the percentage formula, and data analysis in the third problem formulation uses the product moment formula. The results of this study are that the first application of the mudarosah method is included in the good category with a percentage of 78%, the second level of students' reading skills of the Qur'an is in the good category, with a percentage of 76%, and the third is the correlation between the mudarosah method and the reading skills of Al-Qur'an. -The Qur'an is the result of 0.699. Because r count > from rtable 0.284. So it can be said that there is a correlation between the mudarosah method and the reading skills of the VIII graders of the Qur'an.